The Relationship of Self-Concept and Logical Thinking Patterns with Digital Literacy Ability - Yayan Alpian; M. Syarif Sumantri; Yufiarti; Sri Wulan Anggraeni (Indonesian Journal of Social Research (IJSR), 2022)
This study discusses the relationship between self-concept, logical thinking patterns, and digital literacy ability. The research respondents were elementary school teacher education students at the Se University of West Java from initial to final levels without distinguishing gender. Respondents were selected randomly using the proportional random sampling technique. The research data was obtained through a questionnaire on a scale of 0-1 for logical thinking patterns and 1-5 for self-concept and digital literacy ability. The results of this study indicate: that first, there is a positive relationship between self-concept and digital literacy ability of 0.563. Second, a positive relationship exists between logical thinking patterns and digital literacy ability of 0.234. Third, a positive relationship exists between self-concept and logical thinking patterns and digital literacy ability of 0.595. This study put forward some suggestions as follows: (1) prospective teacher students can develop self-concept by focusing on themselves, loving themselves, being responsible, having goals, and being able to interact with the social environment to improve digital literacy ability, (2 ) student teacher candidates must have logical thinking patterns by continuing to train themselves through being able to think with logical rules, be able to determine valid conclusions, think systematically in digital literacy ability, (3) prospective teacher students must be able to control self-concept and logical thinking patterns to improve digital literacy ability as a support in the learning process and for improving academic achievement.